P90 Cyclin-dependent kinases 7 and 9 specifically regulate neutrophil transcription and their inhibition drives apoptosis to promote resolution of inflammation. (2nd December 2011) - Rossi, A G; Duffin, R; Haslett, C; Leitch, A E
Abstract : Introduction and Objectives: Terminally-differentiated neutrophils are short-lived but key effector cells of the innate immune response and play a prominent role in the pathogenesis and propagation of many inflammatory diseases including interstitial lung disease. BAL neutrophilia has been correlated with poor outcome in idiopathic pulmonary fibrosis (IPF) and neutrophils are the dominant cell type in acute exacerbations of IPF as well as in diffuse alveolar damage. Non-specific cyclin-dependent kinase inhibitor drugs have previously been shown to resolve neutrophil-dominant inflammation in the murine bleomycin lung injury model an established model of IPF. Here we elucidate the mechanism by which CDK inhibitor drugs mediate neutrophil apoptosis and hence promote resolution of inflammation. Methods: We isolated peripheral blood neutrophils from healthy human donors and performed a variety of experiments including microarray, confocal microscopy and apoptosis assays (flow cytometry, fluorometric assay, DNA ladders and mitochondrial integrity assay and western blotting) to show that specific effects on neutrophil transcriptional capacity are responsible for CDK-inhibitor driven neutrophil apoptosis. Finally we show that specific CDK inhibitors drive resolution of neutrophil-dominant inflammation in the murine bleomycin lung injury model (Histology, BAL analysis). Results: CDK inhibitors drive neutrophil apoptosis. Neutrophil apoptosis is dependent on a critical balance of pro- and anti-apoptotic proteins. Functional transcriptional machinery is present in human peripheral blood neutrophils. CDKs are present in neutrophils and their activity is both demonstrated and modulated with the use of specific CDK inhibitors. Specific CDK inhibition is a successful strategy for the resolution of murine bleomycin lung injury. Conclusion: We highlight a novel mechanism that controls both neutrophil transcription and apoptosis that could be targeted by selective CDK inhibitor drugs to resolve established neutrophil-dominant inflammation.